Knicks don't click : Isiah Thomas illustrates how money can't buy you love - Berri, David J. (FT Press Delivers elements., 2010)
"This Element is an excerpt from Stumbling On Wins: Two Economists Expose the Pitfalls on the Road to Victory in Professional Sports (9780132357784) by David J. Berri and Martin B. Schmidt. Anatomy of a sports disaster: Isiah Thomas and the New York Knicks"--Resource description page.